Molecular analysis of isolates of Salmonella typhi obtained from patients with fatal and nonfatal typhoid fever. - Thong, Kwai Lin; Passey, M.; Clegg, A.; Combs, B.G.; Yassin, R.M.; Pang, T. (American Society for Microbiology, 1996)
Molecular characterization of a total of 52 human isolates of Salmonella typhi from Papua New Guinea was performed by using pulsed-field gel electrophoresis (PFGE) after digestion of chromosomal DNA with three restriction endonucleases, XbaI (5'-TCTAGA-3'), AvrII (5'-CCTAGG-3'), and SpeI (5'-ACTAGT-3'). Of the 52 isolates tested, 11 were obtained from patients with fatal typhoid fever and 41 were obtained from patients with nonfatal disease. The 52 isolates showed limited genetic diversity as evidenced by only three different PFGE patterns detected following digestion with XbaI (patterns X1 to X3; F [coefficient of similarity] = 0.86 to 1.0), four patterns detected following digestion with AvrII (patterns A1 to A4; F =0.78 to 1.0), and two patterns detected following digestion with SpeI (patterns S1 and S2; F = 0.97 to 1.0). Of the 52 isolates, 37 were phage typed, and all belonged to phage type D2. All 11 isolates obtained from patients with fatal typhoid fever were identical (F = 1.0) and possessed the PFGE pattern combination X1S1A1, whereas the 41 isolates from patients with nonfatal typhoid fever had various PFGE pattern combinations, the most common being X2S1A2 (39%), X1S1A1 (24%), and X1S1A2 (15%). Thus, all the isolates from patients with the fatal disease had the X1 and A1 patterns, whereas the majority of the isolates from patients with nonfatal typhoid fever possessed the X2 and A2 patterns. The data suggest that there is an association among strains of S. typhi between genotype, as assessed by PFGE patterns, and the capability to cause fatal illness. Analysis of blood and fecal isolates of S. typhi from the same patient also indicated that some genetic changes occur in vivo during the course of infection.